2012
DOI: 10.4049/jimmunol.1200056
|View full text |Cite
|
Sign up to set email alerts
|

The Endothelial Antigen ESAM Monitors Hematopoietic Stem Cell Status between Quiescence and Self-Renewal

Abstract: Whereas most hematopoietic stem cells (HSC) are quiescent in homeostasis, they actively proliferate in response to bone marrow (BM) injury. Signals from the BM microenvironment are thought to promote entry of HSC into the cell cycle. However, it has been cumbersome to assess cycle status of viable HSC and thus explore unique features associated with division. In this study, we show that expression of endothelial cell-selective adhesion molecule (ESAM) can be a powerful indicator of HSC activation. ESAM levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 57 publications
1
36
0
Order By: Relevance
“…Among the candidate genes present within the Chr9L interval, but not in the Chr9S interval, we found Crtam, which has been associated with diabetes induction in a mouse model of induced autoimmune diabetes and is expressed on some T cell populations (57). Esam, involved in hematopoiesis (58), is also of interest considering that DN T cell proportion is regulated by bone marrow-intrinsic factors (24). Tirap and Tbrg1 are two other genes within the Chr9L interval known to play significant roles in the immune system, which could be candidate genes for defining the proportion of DN T cells and susceptibility to diabetes.…”
Section: Discussionmentioning
confidence: 92%
“…Among the candidate genes present within the Chr9L interval, but not in the Chr9S interval, we found Crtam, which has been associated with diabetes induction in a mouse model of induced autoimmune diabetes and is expressed on some T cell populations (57). Esam, involved in hematopoiesis (58), is also of interest considering that DN T cell proportion is regulated by bone marrow-intrinsic factors (24). Tirap and Tbrg1 are two other genes within the Chr9L interval known to play significant roles in the immune system, which could be candidate genes for defining the proportion of DN T cells and susceptibility to diabetes.…”
Section: Discussionmentioning
confidence: 92%
“…Parathyroid hormone receptors are typically associated with formation of the stem cell niche (57), but we find them to be up-regulated in AML CD34 ϩ cells as well. ESAM was recently reported as a marker that identifies actively cycling human stem cells that do retain long-term reconstitution activity (58), and it will be interesting to determine its role in myeloid leukemias. The hepatocyte growth factor receptor MET has been shown to play an essential role in numerous cancers (59), and it was recently shown that autocrine activation of MET is frequently observed in AML (60).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial-specific adhesion molecule (ESAM) is a novel HSC-specific marker in mice 37,38 . Expression level of ESAM reflects the HSC transition status between quiescence and self-renewal 39 . It is also involved in the VEGFtriggered vascular permeability and Rho-mediated endothelial cell contacts 40 .…”
Section: Article Nature Communications | Doi: 101038/ncomms4431mentioning
confidence: 99%